2017
DOI: 10.3847/1538-4357/aa6d58
|View full text |Cite
|
Sign up to set email alerts
|

The Green Bank Ammonia Survey: First Results of NH3 Mapping of the Gould Belt

Abstract: We present an overview of the first data release (DR1) and first-look science from the Green Bank Ammonia Survey (GAS). GAS is a Large Program at the Green Bank Telescope to map all Gould Belt star-forming regions with A V 7 mag visible from the northern hemisphere in emission from NH 3 and other key molecular tracers. This first release includes the data for four regions in Gould Belt clouds: B18 in Taurus, NGC 1333 in Perseus, L1688 in Ophiuchus, and Orion A North in Orion. We compare the NH 3 emission to du… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
226
3
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 154 publications
(247 citation statements)
references
References 86 publications
16
226
3
2
Order By: Relevance
“…The Orion A molecular cloud has been measured in NH 3 (1,1) and (2,2) with the GBT telescope (beam size ∼30 ′′ ; Friesen et al 2017; this agrees well with our para-H 2 CO (3-2) data.) We compare maps of gas kinetic temperatures derived from para-H 2 CO and NH 3 (2,2)/(1,1) line ratios in Figure 5.…”
Section: Comparison Of Temperatures Derived From H 2 Co and Other Gassupporting
confidence: 78%
See 3 more Smart Citations
“…The Orion A molecular cloud has been measured in NH 3 (1,1) and (2,2) with the GBT telescope (beam size ∼30 ′′ ; Friesen et al 2017; this agrees well with our para-H 2 CO (3-2) data.) We compare maps of gas kinetic temperatures derived from para-H 2 CO and NH 3 (2,2)/(1,1) line ratios in Figure 5.…”
Section: Comparison Of Temperatures Derived From H 2 Co and Other Gassupporting
confidence: 78%
“…The gas kinetic temperatures are derived from para-H 2 CO and NH 3 (2,2)/(1,1) (Friesen et al 2017) line ratios. The beam sizes of para-H 2 CO and NH 3 are both ∼30 ′′ , so we only fit the data for para-H 2 CO and NH 3 , respectively, with distance R > 30 ′′ .…”
Section: Radiation Heatingmentioning
confidence: 99%
See 2 more Smart Citations
“…Millimeter and sub-mm continuum surveys of nearby clouds showed that prestellar cores have masses ∼ 0.1 − 10 M and sizes ∼ 0.01 − 1 pc (e.g., Enoch et al 2006;Johnstone & Bally 2006;Könyves et al 2010;Kirk et al 2013), while the gas dynamics at core scales have been investigated in spectral line observations using dense gas tracers like N2H + , H 13 CO + , or C 18 O (e.g., Ikeda et al 2009;Rathborne et al 2009;Pineda et al 2015;Punanova et al 2018;Chen et al 2019b). In particular, analyses of core kinematics from the recent Green Bank Ammonia Survey (GAS; Friesen et al 2017) shows that many dense cores are not bound by self-gravity, but are pressure-confined Keown et al 2017;Chen et al 2019c;Kerr et al 2019).…”
Section: Introductionmentioning
confidence: 99%